The Servant Leadership of Catholic School Administrators Affecting the Excellence of the Lovers of the Cross of Chanthaburi Catholic Schools - Sripramong, Ditsaraporn; Thongkaew, Siriporn; Yurarach, Subin (Saengtham College Journal, 2025)
The objectives of this research were to 1) study the level of servant leadership among Catholic school administrators and school excellence in schools under The Lovers of The Cross of Chanthaburi Catholic Schools, 2) study the influence of servant leadership of Catholic school administrators on school excellence under The Lovers of The Cross of Chanthaburi Catholic Schools, and 3) propose guidelines for developing servant leadership of The Lovers of The Cross of Chanthaburi Catholic Schools towards school excellence. This study employed a mixed-methods research design, combining quantitative and qualitative approaches. The research focused on ten dimensions of servant leadership; listening, empathy, healing, awareness, persuasion, conceptualization, foresight, stewardship, commitment to growth of people, and building community. The samples group consisted of 269 teachers. Data were collected from questionnaire and focus group discussion using statistics to analyze the data, namely mean, standard deviation, Pearson correlation coefficient and Stepwise Multiple Regression Analysis. The results of this study found that 1) both study the level of servant leadership among Catholic school administrators and school excellence in schools were rated at a high level, 2) the servant leadership dimensions influenced by Catholic identity, three aspects; conceptualization, foresight, and stewardship significantly affected excellence. The correlation coefficient was at 35, and 3) the development guidelines for servant leadership in three aspects; conceptualization, foresight, and stewardship contributed to effective school development planning towards sustainable excellence.